Pendampingan Industri Rumah Tangga Pangan Dalam Implementasi Cara Produksi Pangan Olahan yang Baik (CPPOB) pada Makanan Beku ‘Kebab Isi Daging' di Kabupaten Sidoarjo - Yeda Rachma Ayu Malthufah; Kusuma Scorpia Lestari (Universitas Airlangga, 2023)
Background: Good Manufacturing Practice (GMP) is a reference that explains the procedures to produce processed food so that it is of high quality, safe, and suitable for public consumption. The Food Safety Facilitator's role is to help register the processed products of SME (Small Medium Enterprise) X to obtain an NIE( Nomor Izin Edar) number. Objectives: The SME assistance aims to improve the implementation of GMP so that it can meet the GMP level that meets the requirements of the Regulation of the Head of the Food and Drug Administration on Guidelines for Inspection of Processed Food Production Facilities. Methods: Initial observations were made with a form based on the standards of the Food and Drug Administration to determine the score and value of SME X, then mentoring and training were carried out to correct GMP non-conformities. Results: The first observation of SME X showed that there were aspects that did not comply with the GMP requirements. With several non-conformities obtained, SME X received a grade of D or very poor, so it needs improvement to get an NIE number from BPOM. The results of the final inspection indicated an improvement in the score from D (very poor) to B (good) so that SME X could obtain the NIE number. Conclusions: Assistance and training to SMEs contributed to the improvement of SMEs' GMP implementation scores so that SME X was able to obtain a distribution license number for its food products